Pengaruh Penggunaan Media Digital terhadap Prestasi Belajar Anak - Ahmad Husain; Lisa Afrilia Simarmata (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine the effect of digital media use on children's academic achievement. Rapid technological developments have made digital media a crucial part of the modern educational process. Using a qualitative descriptive approach, this study provides an in-depth description of how digital media is used in learning activities and its impact on student learning outcomes. Data were collected through observations, interviews, and documentation of students, teachers, and parents involved in the technology-based learning process. The results indicate that digital media plays a significant role in increasing children's interest and motivation in learning, enriching their knowledge base, and helping them understand the material more effectively. However, the study also found that excessive, unsupervised use of digital media can lead to decreased concentration, the development of procrastination, and decreased social interaction among students. Therefore, the use of digital media needs to be balanced with guidance and supervision from teachers and parents to ensure its use remains aligned with educational goals. In conclusion, digital media has significant potential to improve children's academic achievement when used wisely, purposefully, and in accordance with each student's individual learning needs.